FORMATION OF PROFESSIONAL MOBILITY OF FUTURE PRIMARY SCHOOL TEACHERS ON THE BASIS OF INTERACTIVE METHODS (European Science Methodical Journal, 2024)
This article considers that the application of interactive methods in the formation of professional mobility of teachers of the future primary class is an effective tool and promotes the regular development of professional mobility, knowledge and professional competencies of future teachers, modeling non-standard situations related to future professional activities, perception of oneself as an active subject of the pedagogical process, feeling